INFLUENCE FACTOR FINANCIAL LITERACY - Irpan Nurhab (Jurnal Ilmiah Raflesia Akuntansi, 2020)
One of the intelligence that modern humans must possess is financial intelligence, namely intelligence in managing personal financial assets. Students generally have greater freedom to make personal decisions in financial matters. However, the current phenomenon does not reflect the level of student financial literacy. This is the maximum money he has. Students need to be equipped with knowledge and expertise in the field of finance and taught ways to manage finances so that students cannot take advantage of this research. This study aims to determine what factors influence the financial literacy of students at the Metro State Islamic Institute. The method used in this study was to take a direct approach to the respondents who were sampled in the study to obtain primary data. The sampling technique in this study used a proportional random sampling technique with data collection techniques using a questionnaire distribution technique. Factor analysis of 17 indicator variables produces 5 forming factors, namely: 1) Management factor, 2) Revenue factor, 3) Budgeting factor, 4) Education factor, and 5) Planning factor. Keywords: Factor Analysis, Financial Literacy, Multivariate Analysis